The Law of Interfaith Marriage in the Perspective of Quraish Shihab: Analysis of the Interpretation of Surah Al-Baqarah Verse 221, Al-Mumtahanah Verse 10, and Al-Maidah Verse 5 - Iskandar, Iskandar (Jurnal Penelitian Ilmu Ushuluddin, 2025)
Interfaith marriage in Islam is a controversial issue addressed in the Qur'an, with several verses prohibiting marriage to polytheistic women while allowing exceptions for women from the People of the Book. Therefore, it is essential to understand M. Quraish Shihab's interpretation in this context. This study aims to analyze M. Quraish Shihab's views on the legality of interfaith marriage through the interpretation of Qur'anic verses, as well as to examine the relevance of his interpretations to this issue in contemporary Muslim society. The research method employed is library research with a thematic interpretation approach, analyzing three Qur'anic verses related to the legality of interfaith marriage through M. Quraish Shihab's tafsir. M. Quraish Shihab's perspective on the legality of interfaith marriage permits Muslim men to marry women from the People of the Book, provided they maintain their honor, while still prioritizing Muslim women and prohibiting marriage to polytheists. His interpretation is relevant in the context of contemporary Muslim society, offering guidance on appreciating differences while adhering to Islamic values and maintaining family harmony. Recommendations for future researchers relate to the exploration of the meaning of "mushrik" in the Qur'an, particularly concerning the prohibition of marrying those who are mushrik.